IMPLEMENTASI PENDIDIKAN KARAKTER RELIGIUS DI SEKOLAH DASAR STUDI KASUS DI SD NEGERI BANGKOK BOYOLALI - Ristiya Krisnawati (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2025)
Religious character education holds a crucial role in shaping students’ holistic development, encompassing moral, spiritual, and social dimensions. Within the context of elementary education, religious values serve as an essential foundation for developing virtuous behavior and strengthening students’ spiritual awareness. Nevertheless, the implementation of religious character education at the primary level often encounters challenges, particularly in ensuring consistency, environmental support, and parental engagement. Addressing these issues, this study aims to explore in depth the implementation of religious values at SD Negeri Bangkok, Boyolali, and to analyze the strategies adopted by teachers and school principal in fostering students’ religious character. This research employed a qualitative approach using a descriptive method, with data collected through observation, in-depth interviews, and documentation. The data were analyzed using source and method triangulation to enhance validity and credibility. The findings reveal that the implementation of religious character education at SD Negeri Bangkok is conducted holistically across intracurricular, cocurricular, and extracurricular activities. Programs such as Tahfidz Juz 30, congregational Dhuha prayer, morning Tadarus, and Friday Charity have proven effective in nurturing students’ discipline, honesty, responsibility, and social empathy. The success of these programs is sustained by teachers’ dedication, the principal’s support, and the active participation of parents, whereas challenges primarily involve students’ varied capabilities and limited time allocation for mentoring activities. Theoretically, this study strengthens the understanding that effective religious character education requires synergistic collaboration between schools, families, and learning environments to build a sustainable culture of religiosity within the educational context.